One-Pot Synthesis of Spiro-2H-pyrroles from N-Propargylic β-Enaminones - Karadeniz, Eda; Zora, Metin (Synlett, 2019)
A simple and general one-pot method for the synthesis of spiro-2H-pyrroles has been developed. Initially, cyclohexane-embedded β-enaminones with internal alkyne functionality were synthesized by conjugate addition of 1-ethynylcyclohexylamine to α,β-alkynic ketones, followed by palladium-catalyzed coupling of the resulting N-propargylic β-enaminones with aryl iodides. When subjected to basic conditions, the cyclohexane-embedded β-enaminones with internal alkyne functionality underwent tandem nucleophilic cyclization and benzylic C–H oxidation to furnish 3,4-diaryloyl-1-azaspiro[4.5]deca-1,3-diene derivatives in good yields.
Keywords: pyrrole; 2H-pyrrole; N-propargylic β-enaminones; spiro compound; nucleophilic cyclization; benzylic C–H oxidation